TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Engineering strategies for the biosynthesis of rare sugars in microbial cell factories - Heming Xu; Ran Lu; Mei-Li Sun; Lu Lin; Kaifeng Wang; Xiao-Jun Ji (World Journal of Microbiology and Biotechnology, 2026)

Network-driven prioritization of high-impact sectors for the low-carbon transportation system - Wenju Sun; Yao Wang; Qiang Yue; Yisong Wang; Wenqiang Sun; Tao Du; Heming Wang (Journal of Cleaner Production, 2026)

Characteristics of atmospheric CH4, CO2 and CO at a suburban coastal site in Hong Kong - Wai Ming Chan; Dasa Gu; Ka Fung Leung; Yuchen Mai; Sin Ka Mak; Xin Li; Xiangyunong Cao; Zhenxing Liang; Tsz Ching Tse; Zijie Xu; Hao Sun; Heming Bai; et al. (Atmospheric Environment, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

A decade of ecological and environmental research on the belt and road initiative: Evolution and future directions - Yongyue Gong; Heming Wang; Asaf Tzachor; Tomer Fishman; Fengmei Ma; Lingli Hou; Yao Wang; Wenju Sun; Yihan Song; Kai Fang; Wei-Qiang Chen; Yuri Mazei; et al. (Resources, Conservation and Recycling, 2025)

The evolution of research at the intersection of industrial ecology and artificial intelligence - Yongyue Gong; Fengmei Ma; Heming Wang; Asaf Tzachor; Wenju Sun; Junming Zhu; Gang Liu; Heinz Schandl (Journal of Industrial Ecology, 2025)
The intersection of artificial intelligence (AI) and industrial ecology (IE) is gaining significant attention due to AI's potential to enhance the sustainability of production and consumption systems. Understanding the current state of research in this field can highlight covered topics, identify trends, and reveal understudied topics warranting future research. However, few studies have systematically reviewed this intersection. In this study, we analyze 1068 publications within the IE–AI domain using trend factor analysis, word2vec modeling, and top2vec modeling. These methods uncover patterns of topic interconnections and evolutionary trends. Our results identify 71 trending terms within the selected publications, 69 of which, such as “deep learning,” have emerged in the past 8 years. The word2vec analysis shows that the application of various AI techniques is increasingly integrated into life cycle assessment and the circular economy. The top2vec analysis suggests that employing AI to predict and optimize indicators related to products, waste, processes, and their environmental impacts is an emerging trend. Lastly, we propose that fine‐tuning large language models to better understand and process data specific to IE, along with deploying real‐time data collection technologies such as sensors, computer vision, and robotics, could effectively address the challenges of data‐driven decision‐making in this domain.

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

Bridging environmentally extended input-output models and complex network analysis: A bibliometric analysis of trends and opportunities - Wenju Sun; Fengmei Ma; Asaf Tzachor; Yao Wang; Yongyue Gong; Chao Wang; Xiaoqian Hu; Heming Wang (Journal of Cleaner Production, 2025)

Scenario analysis of waste tires from China's vehicles future - Di Cui; Zihan Bi; Yao Wang; Yilu Gu; Heming Wang; Xiaofeng Gao; Peng Wang; Xin Sun; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Visually evaluating drug efficacy in living cells using COF-based fluorescent nanoprobe via CHA amplified detection of miRNA and simultaneous apoptosis imaging - Chuandong Ge; Zhe Chen; Heming Sun; Ping Sun; Jiayin Zhao; Yanjuan Wu; Jing Xu; Mingyang Zhou; Mingming Luan (Analytica Chimica Acta, 2024)

Research on NO generation characteristics of ammonia-premixed flame - Qiaoqun Sun; Yukai Li; Yu Zhang; Jianmin Gao; Heming Dong; Dongdong Feng; Zheng Chen; Shaozeng Sun (Science of The Total Environment, 2023)

What Iodine Intervention Measures Should Be Taken in Different Water Iodine Areas? Evidence from a Cross-sectional Chinese Survey - Yang Du; Peng Liu; Fangang Meng; Lijun Fan; Qingzhen Jia; Weidong Li; Wen Jiang; Jing Ma; Heming Zheng; Peihua Wang; Dianjun Sun; Hongmei Shen (Biological Trace Element Research, 2022)